Proteomics as a Tool for the Study of Mitochondrial Proteome, Its Dysfunctionality and Pathological Consequences in Cardiovascular Diseases - Stastna, Miroslava (International journal of molecular sciences, 2023)
The focus of this review is on the proteomic approaches applied to the study of the qualitative/quantitative changes in mitochondrial proteins that are related to impaired mitochondrial function and consequently different types of pathologies. Proteomic techniques developed in recent years have created a powerful tool for the characterization of both static and dynamic proteomes. They can detect protein-protein interactions and a broad repertoire of post-translation modifications that play pivotal roles in mitochondrial regulation, maintenance and proper function. Based on accumulated proteomic data, conclusions can be derived on how to proceed in disease prevention and treatment. In addition, this article will present an overview of the recently published proteomic papers that deal with the regulatory roles of post-translational modifications of mitochondrial proteins and specifically with cardiovascular diseases connected to mitochondrial dysfunction.
Keywords: posttranslační úpravy proteinů; Mitochondria; proteom; cardiovascular disease; Proteome; lidé; proteomika; mitochondriální proteiny; Protein Processing, Post-Translational; post-translational modifications; proteomics; mitochondrie; Proteomics; Cardiovascular Diseases; mitochondrial proteins; mitochondrial dysfunction; kardiovaskulární nemoci; Mitochondrial Proteins; Humans